The role of mental health variables and coping strategies in premenstrual syndrome. Issue 3 (3rd March 2020) - Aperribai, Leire; Alonso-Arbiol, Itziar
Abstract: In this study we aimed to examine the relationship between PMS and some mental health variables (anxiety, depression, neuroticism) and coping strategies. We analyzed their predictive value by assessing 55 women's symptoms. We found that all the studied health variables and coping strategies were significantly correlated with reported PMS's Negative Symptomatology scores in the premenstrual phase. Interdisciplinary training programs on instrumental coping strategies might be carried out. In future studies researchers might examine how severe Depression would impact on PMS, and which specific intervention strategies would diminish PMS's distressing effects on women's quality of life worldwide.